Molecular Epidemiology of Rubella Virus Strains Detected Around the Time of the 2012–2013 Epidemic in Japan - Mori, Yoshio; Miyoshi, Masahiro; Kikuchi, Masayuki; Sekine, Masao; Umezawa, Masahiro; Saikusa, Miwako; Matsushima, Yuki; Itamochi, Masae; Yasui, Yoshihiro; Kanbayashi, Daiki; Miyoshi, Tatsuya; Akiyoshi, Kyoko; et al. (Frontiers in Microbiology, 2017)
A nationwide rubella epidemic occurred from 2012 to 2013 in Japan, resulting in around 17,000 rubella cases and the birth of 45 infants with congenital rubella syndrome. The aim of this study was to genetically characterize the rubella viruses circulating around the time of the epidemic in Japan. In total, 221 rubella virus strains detected from 14 prefectures in Japan between 2010 and 2014 were sequenced in the 739 nucleotide-window region within the E1 gene. The virus strains were chronologically and geographically characterized into groups based on phylogenetic analysis. Among the 221 strains analyzed, 192 (87%), 26 (12%) and 3 (1%) strains were classified into genotypes 2B, 1E and 1J, respectively. The majority (n=184) of the genotype 2B strains belonged to lineage 2B-L1 and shared nucleotide homology with the strains detected in Southeast and East Asian countries. Phylogenetic analyses demonstrated that at least six distinct clusters of rubella virus strains (clusters 1–6) induced outbreaks in Japan between 2010 and 2014. Among them, strains from clusters 3, 4 and 6 circulated almost simultaneously during 2012–2013. The cluster 3 strains circulated locally, whereas strains from cluster 4 spread nationwide. The findings suggest that rubella viruses were introduced into Japan many times from neighboring countries. The 2012–2013 epidemic was a complex of outbreaks induced by at least three clusters of rubella virus strains.